2020
DOI: 10.1002/rcm.8908
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of synthetic cannabinoid 5F‐ADB and identification of metabolites in authentic human blood samples via human liver microsome incubation and ultra‐high‐performance liquid chromatography/high‐resolution mass spectrometry

Abstract: Indazole carboxamide synthetic cannabinoids, a prevalent class of recreational drugs, are a major clinical, forensic and public health challenge. One such compound, 5F-ADB, has been implicated in fatalities worldwide. Understanding its metabolism and distribution facilitates the development of laboratory assays to substantiate its consumption. Synthetic cannabinoid metabolites have been extensively studied in urine; studies identifying metabolites in blood are limited and no data on the metabolic stability (ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
(164 reference statements)
1
17
0
Order By: Relevance
“…5F-ADB undergoes extensive hepatic metabolism. Results of metabolism studies with pooled human liver microsomes (pHLM) as well as results of both blood and urine screenings have been previously published [ 22 , 53 , 63 , 68 , 69 ]. According to the literature, the metabolism of 5F-ADB is dominated by ester hydrolysis, defluorination (revealing the N -(5-OH-pentyl) metabolite) and monohydroxylations.…”
Section: Introductionmentioning
confidence: 99%
“…5F-ADB undergoes extensive hepatic metabolism. Results of metabolism studies with pooled human liver microsomes (pHLM) as well as results of both blood and urine screenings have been previously published [ 22 , 53 , 63 , 68 , 69 ]. According to the literature, the metabolism of 5F-ADB is dominated by ester hydrolysis, defluorination (revealing the N -(5-OH-pentyl) metabolite) and monohydroxylations.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the metabolites is very challenging as the concentrations of the metabolites are very low and some of them are unpredictable. The development of mass spectrometry, especially high‐resolution mass spectrometry, has facilitated the identification of the metabolites through the measurements of the exact masses, elemental compositions and the product ions 15–17 …”
Section: Introductionmentioning
confidence: 99%
“…The development of mass spectrometry, especially high-resolution mass spectrometry, has facilitated the identification of the metabolites through the measurements of the exact masses, elemental compositions and the product ions. [15][16][17] Therefore, the goal of the present study was to identify the metabolites of MOA produced by rat, monkey and human liver microsomes and hepatocytes by using ultra-high-performance liquid chromatography coupled to quadrupole-orbitrap high-resolution mass spectrometry (UPLC/HRMS) and to propose the metabolic pathways. Acetonitrile (HPLC grade) was obtained from Merck (Darmstadt, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Liver microsomes and hepatocytes derived from the liver tissue are widely used for drug metabolism study as they retain most of the drug‐metabolizing enzymes, such cytochrome P450 enzymes and glucuronosyltransferases 17,18 . In addition, it has been previously demonstrated that high‐resolution mass spectrometry is a powerful technique for metabolite identification due to its high resolution, sensitivity, and high throughput, which facilitates the identification of drug metabolites through the measurements of accurate mass, elemental composition, and the product ions 19,20 …”
Section: Introductionmentioning
confidence: 99%